Removal of microparticles and bacterial inactivation in freshwater RAS by use of foam fractionation, H2O2 and NaCl. (23rd February 2022) - Jafari, Leila; de Jesus Gregersen, Kim Joao; Vadstein, Olav; Pedersen, Lars‐Flemming
Abstract: Foam fractionation (FF) is an effective water treatment technology used to remove fine particles in seawater recirculating aquaculture systems (RAS). However, there is only limited available information on the operation and efficiency of FF in freshwater. This study investigated the treatment efficiency of FF by measuring changes in bacterial activity and microparticle densities in freshwater from RAS. Thirty‐six separate batch tests were performed with FF separately and in combination with addition of hydrogen peroxide (H2 O2 ) and salt (NaCl). Both chemicals are commonly used for water treatment in freshwater aquaculture. The experiment was a 2 × 2 × 3 factorial design with 3 factors: FF (present or absent), H2 O2 (0 or 10 mg L ⎻1 ) and NaCl (0, 3, or 10 ppt). FF reduced the concentration of microparticles and turbidity in freshwater by 58.7 ± 5.4% and 27.5 ± 3.8% respectively. H2 O2 had a significant antimicrobial effect, and the combination of H2 O2 and FF resulted in an 80% reduction in bacterial activity in freshwater. Addition of NaCl improved the efficiency of FF by further reducing particle concentration and turbidity two‐fold at 10 ppt compared to 0 ppt. This study provides new knowledge on the potential use of FF to improve the water quality in freshwater RAS, and this was further enhanced by the addition of H2 O2 or NaCl.